2020
DOI: 10.1016/j.cmi.2019.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the association between antibiotic exposure and colonization with extended-spectrum β-lactamase-producing Gram-negative bacteria using machine learning methods: a multicentre, prospective cohort study

Abstract: Extended-spectrum b-lactamaseIncidence rate Machine learning a b s t r a c t Objectives: The aim of the study was to measure the impact of antibiotic exposure on the acquisition of colonization with extended-spectrum b-lactamase-producing Gram-negative bacteria (ESBL-GNB) accounting for individual-and group-level confounding using machine-learning methods. Methods: Patients hospitalized between September 2010 and June 2013 at six medical and six surgical wards in Italy, Serbia and Romania were screened for ESB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 32 publications
2
42
0
1
Order By: Relevance
“…Other studies have shown a strong relationship between the usage of third-generation cephalosporin and expression of ESBL phenotype [3,15,16]. Tacconelli et al [3] reported that cephalosporin monotherapy ranked first among all antibiotics in promoting colonization of ESBL gram-negative bacteria in rectal swabs through analyzing the patient-level data with machine learning methods. However, in our study, this correlation was not evident.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown a strong relationship between the usage of third-generation cephalosporin and expression of ESBL phenotype [3,15,16]. Tacconelli et al [3] reported that cephalosporin monotherapy ranked first among all antibiotics in promoting colonization of ESBL gram-negative bacteria in rectal swabs through analyzing the patient-level data with machine learning methods. However, in our study, this correlation was not evident.…”
Section: Discussionmentioning
confidence: 99%
“…In this section, we describe a case example of a recent study exploiting he use of ML algorithms for depicting the risk of colonization [19] by extended-spectrum β-lactamases (ESBL)-producing Enterobacterales (ESBL-PE), a type of MDR-GNB. Indeed, although colonization by MDR-GNB is not always followed by MDR-GNB infection (i.e., colonized patients may not develop infection), the latter usually follows the former.…”
Section: Algorithms For Predicting the Risk Of Developing Mdr-gnb mentioning
confidence: 99%
“…The study performed by Tacconelli and colleagues is a good example of combining classical statistical techniques and ML algorithms to provide useful complementary information [19]. First, the authors used flexible parametric survival models (adjusted for colonization pressure and ward of hospital stay) and identified previous antibiotic exposure as one of the independent predictors of ESBL-PE colonization (hazard ratio 2.38, 95% confidence intervals [CI] 1.29-4.40, p = 0.006).…”
Section: Algorithms For Predicting the Risk Of Developing Mdr-gnb mentioning
confidence: 99%
See 1 more Smart Citation
“…Various classes of antibiotics have been described as risk factors for the prevalence of ESBL-producing organisms, including cephalosporins, carbapenems, and trimethoprim/sulfamethoxazole 2 , 3 . These previous studies were based on the concept that using antimicrobial drug results in selective pressure toward the emergence of resistance 4 .…”
Section: Introductionmentioning
confidence: 99%